Case Report: Exploring the underlying mechanisms of psoriasis comorbid with sarcoidosis: insights from a case of coexisting immune-related disorders - Zhen, Yingbao; Liang, Xinlin; Huang, Dawei; Ding, Yangfeng; Shi, Yuling; Yu, Qian (Frontiers in Immunology, 2025)
Psoriasis, a chronic inflammatory disease characterized by hyperactivation of the Th1/Th17 axis, is increasingly recognized for its comorbid mechanisms with other immune-related disorders. This article reports a rare case. The case involves a 62-year-old woman with a 30-year history of chronic plaque psoriasis who developed sudden annular nodules on both lower limbs. Histopathology revealed non-caseating epithelioid granulomas, and PET-CT confirmed multi-system involvement, leading to a diagnosis of sarcoidosis. After three months of oral MTX therapy, the sarcoidosis skin lesions and psoriatic lesions showed significant improvement. The rare instance of coexistence suggests that chronic Th-cell immune activation may disrupt immune homeostasis through distinct pathways. This study presents clinical insights for an understanding of the mechanisms underlying immune-related comorbidities. It emphasizes the importance of implementing dynamic immune monitoring in the management of chronic inflammatory skin diseases